Perceived ease of use, trust, dan customer satisfaction sebagai prediktor terhadap repurchase intention - Yanico, Yanico; Keni, Keni (Universitas Kristen Maranatha, 2021)
This study aimed to determine wheteher or not the perceived ease of use, trust, and customer satisfaction can predict repurchase intention at the e-commerce industry in Jakarta. This study applies online questionnaires that are distributed electronically for data collection. In data collection, 195 respondents participed in filling out the questionnaire, and 176 data could be processed in data processing. Data processing in this study used the PLS-SEM approach, which is using the help of SMART PLS software. Based on the results of data analysis in this study, researchers concluded that the perceived ease of use, trust, and customer satisfaction are significant in predicting repurchases intentions. The results of this research are expected to be information for e-commerce companies to establish strategies related to the use of applications in improving the ease of use of e-commerce applications in the form of ease of product search and ease of payment processing and delivery. In addition, the results of the research are expected that e-commerce companies can provide reliable services and reliable and guaranteed security systems to increase customer trust. Furthermore, e-commerce companies can develop various marketing programs to improve customer satisfaction.